A review on communication issues related to the process and treatment for breast cancer patients in Malaysia - Mohd Jamil, Saidatun Najmiah; Bolong, Jusang; Osman, Mohd Nizam; Tham, Jen Sern (Human Resource Management Academic Research Society, 2021)
Apart from the assistance from medical technology, the process and treatment for breast cancer patients are also closely related to the information perceived by the patients themselves. By stating this, consideration towards communication issues should then be taken into account. This article focuses on the most notable issue discussed in Malaysia in which the communication between breast cancer patients with family members, particularly the communication with the patient's partner effects the process and the treatment that they receive. The study in this article is needed to address the communication issues thus finding solutions which will help to reduce the stigma of breast cancer in Malaysia.